2016
DOI: 10.3390/ijms17111919
|View full text |Cite
|
Sign up to set email alerts
|

A Mixture of Extracts of Kochia scoparia and Rosa multiflora with PPAR α/γ Dual Agonistic Effects Prevents Photoaging in Hairless Mice

Abstract: Activation of peroxisome proliferator-activated receptors (PPAR) α/γ is known to inhibit the increases in matrix metalloproteinase (MMP) and reactive oxygen species (ROS) induced by ultraviolet light (UV). Extracts of natural herbs, such as Kochia scoparia and Rosa multiflora, have a PPAR α/γ dual agonistic effect. Therefore, we investigated whether and how they have an antiaging effect on photoaging skin. Eighteen-week-old hairless mice were irradiated with UVA 14 J/cm2 and UVB 40 mJ/cm2 three times a week fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Consequently, MMPs also play a key role in photoaging, whose synthesis is increased after UV exposure [182]. Results from Jeon et al [183] agreed with this hypothesis: they observed that Rosa multiflora extracts act as PPAR-α agonist which induced a decrease in MPP expression levels, ameliorating photoaging-related effects on murine skin.…”
Section: Rose Hip and Diseasementioning
confidence: 95%
“…Consequently, MMPs also play a key role in photoaging, whose synthesis is increased after UV exposure [182]. Results from Jeon et al [183] agreed with this hypothesis: they observed that Rosa multiflora extracts act as PPAR-α agonist which induced a decrease in MPP expression levels, ameliorating photoaging-related effects on murine skin.…”
Section: Rose Hip and Diseasementioning
confidence: 95%
“…(Cheng et al, 2016). Studies demonstrated that Rosa multiflora possesses analgesic, anti-arthritic, anti-inflammatory, antioxidative, and bone-preserving activities, serving significantly in treatment of collagen-induced RHA (Guo et al, 2011;Jeon et al, 2016;Nakamura et al, 2018;Park et al, 2011;Wu et al, 2014).…”
Section: Davallia Bilabiatementioning
confidence: 99%
“…In addition, the extracts of KF, including total flavonoid, saponin, and phenolic, were proved to have a good antioxidant activity by measuring free radical scavenging activities with ABTS, DPPH, or FARP assay [ 47 – 50 ]. Scavenging free radicals play a key role in aging and inflammation [ 51 ]. Therefore, its antioxidant effects need to be further studied on these aspects.…”
Section: Pharmacologymentioning
confidence: 99%